Central depressant effects of Piper tuberculatum Jacq essential oil in mice. (August 2022) - dos Santos Sales, Valterlúcio; Cabral, Francisco Romero; do Nascimento Sales, Emmily Petícia; Carvalho, Tatyelle Bezerra; Costa, Maria Haiele Nogueira; de Oliveira, Victor Afonso Pereira; de Souza Rodrigues, Cristina Kelly; de Figueirêdo, Francisco Rodolpho Sobreira Dantas Nóbrega; Bezerra, Daniel Souza; de Araújo Delmondes, Gyllyandeson; Coutinho, Henrique Douglas Melo; Costa, José Galberto Martins da; et al.
Abstract: This study aims to investigate the toxicity and possible effects and mechanism of action of the essential oil obtained from the Piper tuberculatum Jacq.'s fruit (EOPT) on the central nervous system (CNS) of mice. In the Hippocratic test, it was observed ambulation reduction, sedation, piloerection and mortality of 25% at the dose of 1000 mg/kg and 50% at the dose of 5000 mg/kg. The results found demonstrate that the EOPT is endowed with a possible depressant effect, and is characterized by a likely sedative (open field test), anxiolytic-like (elevated plus maze test), anticonvulsant (pentylenetetrazole-induced seizure test) and hypnotic action (pentobarbital-induced sleeping time). These effects may possibly occur due to the interaction between the monoterpenes, present in its essential oil, and the GABAergic pathway confirmed by reversion of the effects by flumazenil. Then, these results demonstrate the therapeutic potential and the validation of the ethnopharmacological use of this species in the treatment of disorders affecting the central nervous system.